Community Program Participation Experience of Peer Recovery Coaches for Substance Use Disorders Based on a Caring Perspective: A Qualitative Study - Kyung Im Kang; Chan Mi Kang (Nursing Open, 2026)
ABSTRACT Aim To identify peer recovery coaches' activities from a care perspective to help determine the essential care elements for substance use disorders in Korea. Design Descriptive qualitative study. Methods Using purposive sampling, data were collected through one‐on‐one interviews conducted from November 2023 to May 2024. The transcripts were analysed using deductive content analysis, with the findings structured according to the middle‐range theory of caring framework. Results Peer recovery coaches' program participation experiences were categorized as follows: ‘being a helper with objective insight’, ‘being a companion to move forward together’, ‘being a navigator based on experience’, ‘being a facilitator of recovery who promotes growth’, and ‘being a caregiver with positive values and attitude’. Conclusion Peer recovery coaches facilitate recovery and foster mutual growth within the caring process. For substance use disorder programmes to succeed, nurses must play a pivotal role in designing and implementing these interventions in collaboration with peer recovery coaches. Implications for Nursing Practice The findings lay a foundation for developing nurse‐led interventions that integrate peer recovery coaches into substance use disorder programmes. Specifically, the study offers insights into how nursing professionals can support peer recovery coaches in maintaining personal recovery, accessing institutional support and enhancing their clinical competencies. Impact This study examines the emerging role of peer recovery coaches within South Korean's substance use disorder recovery landscape through the lens of caring theory. The findings offer significant clinical insights for nursing—a field where patient‐centred and team‐based practice is essential—by demonstrating how the lived experiences of peer recovery coaches can integrate with nursing expertise to deliver highly personalized care. Reporting Method The COREQ guidelines were followed. Patient or Public Contribution No patient or public contribution.